METHODS AND MODELS FOR FORMATION A PORTFOLIO OF URBAN TRANSPORT DEVELOPMENT PROJECTS BASED ON THE SMART PORT CITY CONCEPT - Bondar, Alla; Lapkin, Oleksandr (INNOVATIVE TECHNOLOGIES AND SCIENTIFIC SOLUTIONS FOR INDUSTRIES, 2023)
Renovation of public transport fleets was carried out in different cities of the state before the outbreak of hostilities. In year 2020 "Urban public transport of Ukraine II" project was approved by the Government. Among eighteen cities-participants of this project, Odessa was the only one that had a maritime transport usage option. However, the specifics of the territorial location and the experience accumulated by the previous decades in the maritime coastal communications were not taken into account by that project. This article aims to study the specific features of the city’s transport infrastructure development projects portfolio formation with the involvement of the off-street transport modes (including its maritime component), based on the latest Smart Port City concept, which reflects the harmonious targeting of the city and port development main directions. Results. Smart City is the concept, which encourages innovative solutions to the management of all transport types at a particular city level. The carried-out goals systematization reflects the involvement of the city’s public administration and commercial players into the initiation of projects intended to enhance the use of off-street transport types. The ability to initiate a wide range of projects is provided by Smart Port concept to cities where the port operation role is decisive. The combination of these two concepts is presented in the form of Smart Port City, which contains the foundation for a significant number of project initiatives for new products and services in the promising areas of city and port development, improving the quality of urban environment and the port production operations efficiency results. Conclusions. The approach to determine projects structure, which is based on a system of objectives to resolve the city transport problems and ensure the port development, has been proposed. The formalized procedure of projects selection to the portfolio from the Smart Port City perspective has been developed, which allows: first, − to identify projects that match the city and the port general goals; second, − to produce a rating system for the city and the port projects respectively; third, – given the set threshold value, to identify the projects with the highest priority.